A proposed study kit in the new social studies for grade six - Aldemita, Conrada C. 1922- ([Quezon City s.n.], 1974)
This proposed study kit aims to aid the teacher in teaching the new social studies despite the lack of devices. It is also meant to be a prop that can be modified or enriched. For all the teachers, it will give fertile ideas on how to prepare a study kit that will fit into his/her particular mold. Ideas on how to go about preparing a study kit was given. It reflects the new thrusts in the new society and at the same time contributes an instructional material that can be of immediate use in the classroom.
Thesis (M.A.T.)--University of the Philippines.
Keywords: Social sciences -- Study and teaching (Elementary) -- Philippines; Social sciences -- Programmed instruction